Chapter Un'indagine sulla percezione dell'efficacia delle pratiche inclusive dei docenti di scuola secondaria: analisi e integrazione dei dati raccolti con la scala TEIP - MAIENZA, MATTEO (Studies on Adult Learning and Education, 2022)
This study is aimed to report the qualitative data collected as part of a larger evaluation research project on educational contexts for disabilities. The sample consists of 161 pre-service teachers completing their education at the University of Florence, who were asked to indicate strengths and weaknesses in the implementation of their own inclusive teaching practices (TEIP). This study focuses on a few specific areas according to the existing literature that sees teaching practices, collaboration between school staff and families, and behavior management as related elements for defining inclusive environments and attitudes. The integration of quantitative and qualitative data collected and analyzed separately explains all the elements that may contribute to self-efficacy toward school inclusion, such as the subject-specific support teacher preparation and the quality of collaboration within the working group for inclusion whose impact relates to the level of engagements achieved by students that can increase chances of success of the educational project.